Biological Treatment of Crude Oil by Synechococcus sp - Alkhazraji, Marwa Saad; Al-Rawi, Altaf Abed Alwahed; Al-Obaidy, Abdul Hameed M. Jawad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Crude oil is known globally as one of the major causes of environmental pollution. This chemical compound exerts exhausting impacts on cultivable lands and water surfaces, leading to profound damage to agriculture and aquatic life. Over the years, several bioremediation approaches have evolved to manage this pollution problem properly. A phylum of microorganisms known as cyanobacteria offers an efficient alternative to established bioremediation methods. We conducted the present study to investigate the effectiveness of cyanobacteria in eliminating residual total petroleum hydrocarbon (TPH). Synechococcus algae treated three concentrations of crude oil (0.6, 1.8, and 3 ppm) over four time periods (on days 3, 6, 9, and 12). The gas chromatography test showed that on days 3, 6, 9, and 12 of treatment, the percentages of petroleum hydrocarbon removal were 34.66, 65.47, 83.98, and 93.12%, respectively, at a concentration of 0.6 ppm of crude oil. We recorded removal rates of 29.44, 57.42, 80.60, and 90.41% for 1.8 ppm of crude oil, and 30.67, 51.52, 76.38, and 90.74% for 3 ppm on days 3, 6, 9, and 12, respectively. Ultimately, we discovered that cyanobacteria (Synechococcus sp.) are effective biological pollutant removers, effectively eliminating hydrocarbon compounds from the water.